2006
DOI: 10.1093/bja/aei290
|View full text |Cite
|
Sign up to set email alerts
|

Bougie-guided insertion of the ProSeal™ laryngeal mask airway has higher first attempt success rate than the digital technique in children

Abstract: We conclude that bougie-guided insertion of the ProSeal LMA has a higher first attempt success rate than the digital technique in children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
32
0

Year Published

2009
2009
2012
2012

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 24 publications
(37 citation statements)
references
References 13 publications
5
32
0
Order By: Relevance
“…Interestingly, recent reports showed that the GEB had also led to more precise placement of the PLMA compared with IT techniques in children. 8,15 In these reports, children who were allocated to the GEB group had better separation of the gastrointestinal tract from the airway. We were unable to determine which technique of insertion is associated with a higher success rate pertaining to adequate ventilation.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, recent reports showed that the GEB had also led to more precise placement of the PLMA compared with IT techniques in children. 8,15 In these reports, children who were allocated to the GEB group had better separation of the gastrointestinal tract from the airway. We were unable to determine which technique of insertion is associated with a higher success rate pertaining to adequate ventilation.…”
Section: Discussionmentioning
confidence: 99%
“…However, use of the PLMA requires device rotation, GEB-guided insertion technique, or digital Data are expressed as mean ± standard deviation (SD) or number (%) technique [1][2][3]. The i-gel device insertion was easily performed without requiring any special technique, even by residents under supervision.…”
Section: Discussionmentioning
confidence: 99%
“…The Pro-Seal LMA (PLMA) was a ground-breaking invention that enabled drainage of the gastric contents. However, in some cases, use of PLMA required the device rotation method, gum elastic bougie (GEB)-guided insertion technique, and digital technique [1][2][3]. Other issues associated with PLMA were difficult stomach tube insertion and obtaining appropriate sealing pressure [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…4,12,13 In the present study, inexperienced personnel achieved a 78% success rate on their first attempt using the digital technique. Considering inexperienced personnel achieved an 83% first-attempt success rate at LMA ProSeal insertion in adults using the same technique, 2 our results show that LMA ProSeal insertion in children is also challenging for inexperienced personnel.…”
Section: Discussionmentioning
confidence: 50%
“…is an advanced form of the LMA with a softer and larger cuff to improve sealing and a drain tube to permit venting of the stomach. [1][2][3][4] However, when a larger cuff is used, it is more difficult to save space for inserting the LMA ProSeal in the patient's mouth, and the larger cuff is more likely to fold over. 5,6 In particular, LMA ProSeal insertion in pediatric patients may be impeded by a relatively large tongue, a floppy epiglottis, and the frequent presence of tonsillar hypertrophy.…”
Section: Introductionmentioning
confidence: 99%